Renewable resources and renewable energy : a global challenge - Graziani, Mauro; Fornasiero, Paolo, 1968- (CRC Press, 2007)
This volume highlights the role of catalysts in the transformation of renewable starting materials into valuable products. It addresses the fundamental importance of improving the production and use of renewable energy.